Course advisory system (CAS): A solution for assisting students in choosing suitable courses offered by local universities / Norisma Idris and Siong L. C. - Idris, Norisma; Siong, L. C. (2004)
This paper reports how ICT is used to stimulate advancements in providing advice to students for choosing suitable courses offered by local Universities. Course advisory system or CAS is a Web based system aims to help students in making decision regarding the courses they should apply by giving advice base on previous experiences. It represents the decision-making process by using an artificial intelligence technique called case-based reasoning. CAS consists of two main modules which are general module and advisory module. The general module enables users to search for the synopsis of the courses and provides link to relevant websites, while the advisory module is to generate an advice for the users. Besides that, there are three external agents involved in CAS; user, case base and course information database. The user is responsible for entering the problem descriptions and also getting advice from the system; case base contains previous solved cases; and course information database contains the synopsis of the courses.